RIOT.ID: Revolutionizing Running Community Management with Next.js and Gamification - Shaan, Peter; Sihotang, Jay Idoan (CogITo Smart Journal, 2024)
The RIOT Indonesia running community has been actively engaged since 2018, continuing to expand its reach. However, despite this significant growth, the community still relies on manual systems for managing membership and recording activities. Information technology, recognized as a catalyst for transformation across various sectors, including sports, presents an opportunity to enhance the efficiency of community management. This research focuses on the design of the Web RIOT.ID application, a web-based solution that integrates QR Code technology and gamification principles through an Experience Points (XP) system to motivate member participation. The user interface design of the application employs the Design Thinking methodology, ensuring that the solutions developed are tailored to meet user needs. Developed using a Rapid Application Development (RAD) approach, the application leverages Next.js and MongoDB. Evaluation is conducted through black box testing to confirm the application's functionality and its alignment with the established objectives. The RIOT.ID application is expected to serve as a model for other communities aiming to harness information technology to enhance organizational management and member engagement.